Piezo1 Participated in Decreased L-Type Calcium Current Induced by High Hydrostatic Pressure via. CaM/Src/Pitx2 Activation in Atrial Myocytes - Fang, Yuan; Li, Qian; Li, Xin; Luo, Guan-Hao; Kuang, Su-Juan; Luo, Xue-Shan; Li, Qiao-Qiao; Yang, Hui; Liu, Yang; Deng, Chun-Yu; Xue, Yu-Mei; Wu, Shu-Lin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Hypertension is a major cardiovascular risk factor for atrial fibrillation (AF) worldwide. However, the role of mechanical stress caused by hypertension on downregulating the L-type calcium current (ICa,L), which is vital for AF occurrence, remains unclear. Therefore, the aim of the present study was to investigate the role of Piezo1, a mechanically activated ion channel, in the decrease of ICa,L in response to high hydrostatic pressure (HHP, one of the principal mechanical stresses) at 40 mmHg, and to elucidate the underlying pathways. Experiments were conducted using left atrial appendages from patients with AF, spontaneously hypertensive rats (SHRs) treated with valsartan (Val) at 30 mg/kg/day and atrium-derived HL-1 cells exposed to HHP. The protein expression levels of Piezo1, Calmodulin (CaM), and Src increased, while that of the L-type calcium channel a1c subunit protein (Cav1.2) decreased in the left atrial tissue of AF patients and SHRs. SHRs were more vulnerable to AF, with decreased ICa,L and shortened action potential duration, which were ameliorated by Val treatment. Validation of these results in HL-1 cells in the context of HHP also demonstrated that Piezo1 is required for the decrease of ICa,L by regulating Ca2+ transient and activating CaM/Src pathway to increase the expression of paired like homeodomain-2 (Pitx2) in atrial myocytes. Together, these data demonstrate that HHP stimulation increases AF susceptibility through Piezo1 activation, which is required for the decrease of ICa,Lvia. the CaM/Src/Pitx2 pathway in atrial myocytes.